2011
DOI: 10.1149/2.002202esl
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Micromachining of NiTi Shape Memory Alloys with Ultrashort Voltage Pulses

Abstract: Electrochemical micromachining (ECMM) with ultrashort voltage pulses has been used to fabricate microstructures on a NiTi shape memory alloy (SMA). Because of its unique properties, NiTi is a desirable material for use in various applications including medical devices and actuators. ECMM is a heat-free, strain-free, and mask-free method for microfabrication, and therefore well suited for use with shape memory alloys. Microstructures were machined to a depth of 3 μm on NiTi surfaces, and the lateral resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…This method facilitates the preparation technique for large areas and could enable applications of switchable surface arrays in tribology, switchable adhesion, or biomedicine Pulsed Electrochemical Machining plays in important role in NiTi processing due the oxidation and deformation free formation of complex microstructures without thermal damage or distortion . In the present work, we revealed that a formation of different protruding structures on a NiTi surface was possible via PECM using a tool of holes and grooves. We induced a TWSME by compression of surface structures.…”
Section: Discussionmentioning
confidence: 60%
“…This method facilitates the preparation technique for large areas and could enable applications of switchable surface arrays in tribology, switchable adhesion, or biomedicine Pulsed Electrochemical Machining plays in important role in NiTi processing due the oxidation and deformation free formation of complex microstructures without thermal damage or distortion . In the present work, we revealed that a formation of different protruding structures on a NiTi surface was possible via PECM using a tool of holes and grooves. We induced a TWSME by compression of surface structures.…”
Section: Discussionmentioning
confidence: 60%
“…Shin optimized pulse signal parameters such as the voltage peak, pulse duration, and its period, to improve machining accuracy and stability 8 . Maurer fabricated microstructures on NiTi shape memory alloys using the ECMM technique based on ultrashort pulses 9 . Huang developed a nanosecond pulsed electrochemical micromachining system, conducted a series of experiments, studied the effects of pulse signal parameters on machining accuracy, and successfully prepared complex microstructures on nickel and superalloy plates 10 .…”
Section: Introductionmentioning
confidence: 99%
“…There are both conventional and unconventional techniques to produce the microscale features that these devices frequently require on NiTi SMAs [9]. Nevertheless, the efficacy of ECMM as a non-traditional technique for micro-feature machining on Nitinol has already been demonstrated by several authors [10][11][12]. The unique combination properties of ECMM like its non-thermal nature, high precision, customization capabilities, and non-contact operation make it the ideal choice for microfabrication on Nitinol, opening up new possibilities for advanced microscale applications [13,14].…”
Section: Introductionmentioning
confidence: 99%